O assalariamento dos trabalhadores improdutivos nos serviços: fundamentos para compreender a condição de assalariamento - Silva, Jaqueline Lima da (2011)
This dissertation presents a discussion that intends to understand the reality that permeates the profession of social work, addressing the issues concerning to the condition of the unproductive workers in the services, and its main goal to clarify what it means to be an employee engaged in the current way of production. From a literature search, we sought to understand the reasons for the condition of wage, based on Marxian thought. Besides counting on the contributions of contemporary authors, the task of trying to understand the meaning of the condition of wage labor in the capitalism and what their determinations are, examine the abstract work and its relationship to the wage, to investigate the particularities of unproductive labor and find the social function of wage for the unproductive workers. It was analyzed that the salaried work takes as a function, first of all, to hide the relation of exploitation that exists in the process of extraction of surplus value, hiding the division that exists between the necessary work and excess work, in other words, between paid work and work not paid. It was also found that the wage of unproductive worker takes an important legitimizing function in the capitalist system of production, giving conditions for their reproduction, especially acting in control of the workforce. We emphasize that this process presupposes the wage of the proletariat, having in mind that, the proletarian work gives rise to the existent material wealth, without which it would not be possible any form of remuneration.